2015
DOI: 10.1093/cvr/cvv155
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cardiac fibrosis by Krüppel-like factor 6 through transcriptional control of thrombospondin 4 in cardiomyocytes

Abstract: Our present studies on the cardiac function of KLF6 show a new mechanism whereby cardiomyocytes regulate cardiac fibrosis through transcriptional control of the extracellular matrix factor, TSP4, which, in turn, modulates activation of cardiac fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…The expression of TSP-4 in heart tissue was increased in various cardiac disease model animals [12,22,29,30]. Several studies reported that TSP-4 exerted a cardioprotective effect in cardiac diseases [12,30]. In the present study, TSP-4 prolonged APD with suppressing the activation of calcium and potassium channels.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The expression of TSP-4 in heart tissue was increased in various cardiac disease model animals [12,22,29,30]. Several studies reported that TSP-4 exerted a cardioprotective effect in cardiac diseases [12,30]. In the present study, TSP-4 prolonged APD with suppressing the activation of calcium and potassium channels.…”
Section: Discussionsupporting
confidence: 60%
“…The expression of TSP-4 in heart tissue was increased in various cardiac disease model animals [12,22,29,30]. Several studies reported that TSP-4 exerted a cardioprotective effect in cardiac diseases [12,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rock1, two other key regulators of fibrosis. 26,27 This suggests that the molecular mechanism that drive cardiac fibrosis are sensitive to small perturbations in gene expression. Since therapeutical targeting of SOX9 would also moderately lower expression levels, we think this genetic model gives a good representation of what would happen when using an inhibitor of SOX9 in the clinic as a therapy for cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that TSP-4 has a more direct role on the ECM remodeling process [59], but what this role is and the mechanism behind it are currently unclear. Upstream, TSP4 expression is regulated by the transcription factor krüppel-like factor 6 (KLF6) in order to regulate cardiac fibrosis [60] (Figure 2). …”
Section: Matrix Remodeling and Fibrosismentioning
confidence: 99%